Áreas de inundación por ocurrencia de avenidas máximas en la subcuenca Milagros, Yungay, Perú (Aporte Santiaguino, 2023)
Flooding of the agricultural areas and homes of the Cañasbamba hamlet represents a problem due to the overflowing of the waters of the Milagros stream in seasons of extreme rainfall. In this research, the objective is to determine the flooding areas due to the occurrence of maximum flows in the Milagros subbasin. Through hydrological modeling with HEC-HMS 4.9, extreme flows of 9, 11, 13.4, 16.9 and 20 m3/sec have been obtained for return periods of 50, 100, 200, 500 and 1000 years respectively. Field work was carried out to obtain topographic, rheological information and roughness coefficient. Having the flood hydrographs and the field information, we proceeded to hydraulic modeling with FLO-2D for hyperconcentrated flows, where the results showed that the maximum depths reached by the flow are 1.81, 2.04, 2.18, 2.35 and 2.50 m for the aforementioned return periods. The flood areas in the Cañasbamba hamlet have been determined to be 3.43, 3.80, 4.13, 4.60 and 5.23 Ha for the five indicated return periods.